In situ hybridization detection and subtyping of rotaviruses in swine samples. (January 2019) - Resende, Talita P.; Marthaler, Douglas; Vannucci, Fabio A.
Rotavirus groups A, B, and C (RVA, RVB, and RVC, respectively) have been the most prevalent and pathogenic in pigs. To date, immunohistochemistry is only available for RVA because of the lack of commercial antibodies for RVB and RVC. We developed a novel in situ hybridization RNA-based chromogenic technique (ISH-RNA) to detect and subtype RVA, RVB, and RVC. We evaluated 33 samples that were reverse-transcription PCR positive for RVA, RVB, and/or RVC. ISH-RNA was able to detect as few as 10 3 RV RNA copies/mL. The new ISH-RNA test can be useful for routine investigation of rotavirus enteritis in order to guide strategies for control of the infection in pigs, but a full validation study needs to be completed. Pathogenesis studies may be conducted using ISH-RNA based on the identification of replicating virus.